Analysis of Tiktok Content Communication Media on Generation Z Love Relationship of UGJ’s Communication Science’s Students - Chandra, Sekar Kaniar; Nurruzaman, Nurruzaman (Journal of Comprehensive Science, 2025)
This study aims to analyze the influence of TikTok content on the love relationship of generation Z at Ilkom UGJ. This research uses a qualitative approach and case study method, this study identifies the types of content that have a significant impact on the views and attitudes of generation Z towards romantic relationships, forming the mindset and behavior of generation Z at Ilkom UGJ related to romantic relationships. The results of this study show that TikTok, as one of the most dominant social media in the digital era, plays a significant role in shaping the dynamics of love relationships among Generation Z. Through phenomenological approaches and qualitative data collection techniques, it was found that romantic content that is widespread on TikTok is able to influence perceptions, attitudes, and interaction patterns between young couples. both positively and negatively. The conclusion of this study is expected to provide insight into how TikTok The current development of information technology and social media has had a major impact on various aspects of people's lives, including interpersonal relationships, especially among the younger generation. TikTok, as one of the most popular social media platforms, provides a wide range of content that affects the perception and behavior of its users, including in terms of romantic relationships.